Evolution of innate immunity - Kaufman, Jim (Henry Stewart Talks, 2012)
Evolutionary arms race between hosts and pathogens, Evidence and models of adaptive and innate immunity, Methods and data for inferring the evolution of immunity, Toll-like receptors (TLRs), The complement system (C'), Natural killer (NK) cells, Anti-microbial peptides (AMPs), Phagocytes, Diversity in immune responses is a most important property
Reviewed at 2022/01/23